Lattice structures with negative Poisson's ratio: A review. (March 2023) - Xue, Xin; Lin, Congcong; Wu, Fang; Li, Zeyu; Liao, Juan
Abstract: Metamaterials with negative Poisson's ratio (NPR) lattice structures have been of considerable importance and interest in numerous engineering applications. A comprehensive literature review on lattice structure design, mechanical property, manufacturing technique, and deformation mechanism is essential for developing novel metamaterials. Several lattice structure design solutions, including re-entrant structures, chiral structures, and rotating rigid structures, are presented in this work. Secondly, the associated mechanical properties, including static property, indentation strength, and energy absorption, are discussed. The paper then presents some fundamental manufacturing methods for lattice structures with NPR, including additive manufacturing, subtractive manufacturing, casting, snap-fit, and welding, along with the corresponding deformation mechanisms. Finally, the conventional engineering applications such as medical and biomedical applications, aerospace industry, protective devices, strain sensors, and fastener applications are reported, along with a brief overview of the potential applications. Graphical Abstract: ga1 Highlight: Metamaterial structure designs with negative Poisson's ratio lattice structures are reviewed. Multi-functional performances such as mechanical property, energy absorption and thermodynamic characteristics are presented. Manufacturing technologies such as additive manufacturing, casting, snap-fit and welding are introduced. Engineering applications and potentials of lattice structures with NPR in various fields are reported.